PEMBERDAYAAN REMAJA MA MUHAMMADIYAH 2 AL-FURQAN MELALUI EDUKASI PRINSIP DAGUSIBU DALAM PENGGUNAAN SUNSCREEN - Elsa Putri Azzahra; Nabilah Nur Ariqoh Fuadiati; Siti Maimunah; Meina Rizkia; Gibran Maulana Febriannor; Erensha E; Erlina Fatmasari Fatmasari (FIP UNIRA MALANG, 2026)
Excessive exposure to ultraviolet radiation can increase the risk of various skin health problems, particularly among adolescents who have a high level of outdoor activities. Sunscreen is an effective preventive measure to protect the skin from the harmful effects of sun exposure; however, adolescents’ knowledge and behavior regarding the proper use of sunscreen remain relatively low, especially in terms of obtaining, using, storing, and disposing of the product correctly. This community service activity aimed to empower students of MA Muhammadiyah 2 Al-Furqan through education on the DAGUSIBU principles (Obtain, Use, Store, and Dispose) in sunscreen use. The implementation method applied an educational and participatory approach, including initial observation, interactive counseling sessions, demonstrations of proper sunscreen application, and evaluation through pre-test and post-test assessments. The participants consisted of 45 students aged 15–18 years. The results showed an increase in knowledge among all participants, with the average pre-test score rising from 7.64 to 9.84 in the post-test, as well as an increase in the average percentage of correct answers from 67.11% to 97.11%. In addition, most participants reported being satisfied to very satisfied with the materials and the implementation of the activity. Education based on the DAGUSIBU principles proved effective in improving adolescents’ understanding of proper, safe, and responsible sunscreen use and has the potential to encourage sustainable skin health protection behaviors.